Internationalizing studies on mafia journalism. Why including them within journalism studies (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
Organized crime and mafia have been studying by methods that are increasingly rigorous. Within the subfield of mafia journalism, a more solid approach appears to be less evident, despite many contributions on the subject. This article argues the need for a deeper link with the so-called journalism studies, international studies dealing with journalism. The article states that in this context the studies on mafia journalism can find useful theoretical perspectives and methodologies. At the same time, the study of journalism inherent organized crime is a fundamental subfield of the more general studies on journalism.Keywords: journalism, internationalization, media, methods, research